Impacto del covid-19 en la cartera de crédito de las cooperativas de ahorro y crédito del segmento 1 ubicadas en la ciudad de Latacunga en el periodo 2018 - 2021 - Rodríguez Iñiguez, María Fernanda (2022)
The Popular and Solidarity Financial Sector plays a fundamental role for the function of the economy, the arrival of COVID-19 presented a challenge in which savings and credit cooperatives were subject to implement new parameters in order to maintain control of their operations, in this way the present research work seeks to know COVID-19 impact over credit portfolio of COAC’s segment 1. For present development quantitative approach methodology was used, which allowed a horizontal analysis of credit portfolios obtaining comparative result between current and projected data of late payment, coverage and performance. The main literature source from which financial bulletin detailing portfolios status was obtained is SEPS (Superintendence of Popular and Solidarity Economy) similarly, indicators of late payment were obtained from the same body from technical sheet, the same coverage and performance as when it was applied and then performed a horizontal analysis to measure the trend allowed to know the status of each cooperatives at 2016-2021 period resulting in the cooperative with the most impact on late payments in 2019-2021 period considered affected by COVID-19 is savings and credit cooperative Vicentina Manuel Esteban Godoy Ortega because when measuring the default rate in the productive credit portfolio presented a high trend; measuring the impact on the coverage portfolio , it was observed that the cooperative that had the largest reserve to protect the portfolio was the savings and credit union Chibuleo, while, with respect to return rate the National Police’s savings and credit union showed greater profits in relation to the interest charged on credit portfolio Subsequently, an annual projection of the average result obtained from the calculations was made, the same that when compared with the actual data allow to measure the impact of COVID-19 on each of the indicators, showing as results in relation to the rate of late payments a negative impact, the portfolio most affected being that of microcredit, while the portfolio that had the least impact is the real state portfolio, as regards the coverage of the portfolio, the productive credit portfolio decreased, meanwhile the micro-credit portfolio increased, Finally, when measure the return as a result, it was obtained that on average the microcredit portfolio has been the portfolio that has had the highest return since it does not present a significant impact.